Forecasting Indicators of Business Development in Uzbekistan - Akbarov Shokhabbos Khakimjon ugli (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
The article is devoted to econometric modelling and forecasting of business development using correlation and regression analysis. Also, a model for the development of GDP business is given, taking into account the indicators of the share of business in the number of employees in the volume of agricultural production, exports of the Republic of Uzbekistan and the forecast value of the share of business in GDP by 2017-2021.